HIV envelope: challenges and opportunities for development of entry inhibitors - Caffrey, Michael (Elsevier Ltd., 2011)
The HIV envelope proteins glycoprotein 120 (gp120) and glycoprotein 41 (gp41) play crucial roles in HIV entry, therefore they are of extreme interest in the development of novel therapeutics. Studies using diverse methods, including structural biology and mutagenesis, have resulted in a detailed model for envelope-mediated entry, which consists of multiple conformations, each a potential target for therapeutic intervention. In this review, the challenges, strategies and progress to date for developing novel entry inhibitors directed at disrupting HIV gp120 and gp41 function are discussed.